Self-Esteem Profile of Bullying Victims Viewed from the Gender of Middle School Students - Salsabila, Dhea Arischa; Karneli , Yeni (The Future of Education Journal, 2025)
This study is motivated by the differences in self-esteem between male and female bullying victims in schools. The objectives of this study are: 1) to describe the self-esteem of male students at SMP N 13 Padang; 2) to describe the self-esteem of female students at SMP N 13 Padang; and 3) to examine whether there are differences in the self-esteem of male and female students at SMP N 13 Padang. The research method used is quantitative with a descriptive and comparative approach. The sample for this study consisted of 22 bullying victims at SMP Negeri 13 Padang, selected using purposive sampling technique. Data was collected by administering a self-esteem questionnaire to the students. The data was then analyzed using descriptive statistical analysis and t-test for difference testing with a significance level of 5% (= 0.05). The results of the study show that: 1) the self-esteem of male students is in the high category with a percentage of 90.91%; 2) the self-esteem of female students is in the moderate category with a percentage of 72.73%; and 3) there is a significant difference in self-esteem between male and female students with a p-value of 0.006 ≤ 0.05. Based on the research findings, guidance counselors can provide support to enhance and develop students' self-esteem through informational services and group counseling services.